Use of spectral decomposition technique for delineation of channels at Solar gas discovery, offshore West Nile Delta, Egypt - Adel A.A. Othman; M. Fathy; Ali Maher (Egyptian Journal of Petroleum)
This paper presents a case study of spectral decomposition of seismic data and how it aids in seismic data interpretation. It is also known as time–frequency analysis where non-stationary signals in time/space are from time/space domain to time/space vs. frequency domain. The frequency domain representation illustrates many important features that are not apparent in time domain representation. Spectral decomposition is a non-unique process for which various techniques exist and newer modified techniques are being discovered. Over the years, spectral decomposition of seismic data has progressed from being a tool for stratigraphic analysis to helping as a Direct Hydrocarbon Indicator (DHI); a potential weapon for reducing dry well drilling. In the coming years, it is expected that spectral decomposition may be able to play a significant role in analyzing time lapse seismic data. In this paper, spectral decomposition technique is applied to the imaging and mapping of bed thickness, geologic discontinuities and channel delineation at Solar discovery. From the study, two distinctively different channels (gas bearing “Red channel” and water bearing “Yellow channel”) were delineated in the area, and are proven by the drilled well, and some stratigraphic features are identified.